Scriptural Incipits on Amulets from Late Antique Egypt: Text, Typology, and Theory - Sanzo, Joseph E. (Studien und Texte zu Antike und Christentum Studies and Texts in Antiquity and Christianity, 2014)
Cover -- Preface -- Table of Contents -- List of Abbreviations -- Critical Signs -- Introduction -- I. Survey of Scholarship -- II. Toward a New Approach to the Scriptural Incipits -- III. Rethinking the Category "Christian" Amulets -- IV. Section and Chapter Summaries -- Section 1: A Typology of Scriptural Incipits -- Chapter 1: On the Relation pars pro toto -- I. Pars pro toto, Metonymy, and Synecdoche -- II. Meronymic Relations -- II. 1. Meronymy and the Scriptures -- II. 2. Larger Scriptural Units -- II. 2. a. The Meronymic Status of the "Bible" -- II. 2. b. The Meronymic Status of the Gospels -- II. 2. c. Conclusions: The "Bible" and Its Sub-Corpora -- II. 3. Smaller Scriptural Units -- II. 3. a. The Meronymic Status of Biblical Psalms -- II. 3. b. The Meronymic Status of the Lord's Prayer -- II. 3. c. Conclusions: Smaller Scriptural Units -- III. Conclusions -- Chapter 2: The Use of Scripture on Amulets: Relevance and the Power of Precedent -- I. The Hierarchical Approach to the Scriptures on Amulets -- I. 1. "Relevance" and Scriptural Passages in Demonic Struggle -- I. 2. The Hierarchical Approach to Literature and the Late Antique Miscellany -- II. Hierarchy and Historiolae: The Power of Precedent and Paradigm -- III. Conclusions -- Excursus: The Hierarchical View of Scripture and Ritual Authority -- Section 2: A Collection of Scriptural Incipits -- Chapter 3: Potential Incipits of Multiunit Corpora -- I. The Gospel Incipits -- I. 1. Ritual Artifacts with at least the Four Gospel Incipits -- I. 2. Ritual Artifacts with Two or Three Gospel Incipits -- I. 3. Ritual Artifacts with One Gospel Incipit -- II. Other Possible Incipits of Multiunit Corpora -- III. Patterns and Trends -- IV. Conclusions -- Chapter 4: Potential Incipits of Single-unit Texts -- I. Psalmic Incipits -- I. 1. Incipits of LXX Ps 90 -- I. 2. Other Psalmic Incipits.